Prevention of Injuries and Overuse in Sports Directory for Physicians, Physiotherapists, Sport Scientists and Coaches - Mayr, Hermann O.; Zaffagnini, Stefano; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book, published in cooperation with ESSKA, is a comprehensive, evidence-based manual on the prevention of injuries and overuse in sports that will assist physicians, physiotherapists, and trainers in providing excellent mental and physical guidance to athletes. The causes of overuse and sports injuries are carefully analyzed, explaining the medical basis for prevention. In addition, detailed attention is paid to the relationship between sport motivation, risk willingness, tendency to overload, and tendency to increased risk of injury. The reader is effectively trained in mental and physical analysis of the athlete and will gain an appreciation of the influence of the athlete$1 (Bs environment on susceptibility to injury. Gender-specific differences and the specific risks faced by children and adolescents are identified, and very popular sports such as soccer, alpine skiing, and throwing sports are discussed in individual chapters. Training schedules of value in the context of particular physiotherapeutic and medical interventions are described with the help of illustrations and charts. The authors are team physicians, coaches, sports scientists, training scientists, and physiotherapists involved in high-performance sports and recreational sports.s
Major causes of sports injury -- Causes of overuse in sports -- General prevention principles of injury -- General prevention principles of overload damage -- Special aspects of prevention in children and adolescents -- General training aspects in consideration of prevention -- Specific aspects of throwing sports in recreational and competitive sport -- Specific aspects of soccer in recreational and competitive sport (UEFA, FIFA) -- Specific aspects of alpine skiing in recreational and competitive sport (FIS) -- Implementation of prevention in sports.
Keywords: Medicine; Human physiology; Orthopedics; Sports medicine; Physiotherapy; Medicine & Public Health; Sports Medicine; Surgical Orthopedics; Conservative Orthopedics; Physiotherapy; Human Physiology; Electronic books